Investigation on the Breakdown Characteristics of Different Types of Lightning Rods - Ahmad, Noor Azlinda; Zainal, Rosniza; Adzis, Zuraimy (ELEKTRIKA- Journal of Electrical Engineering, 2018)
This paper investigates the voltage breakdown characteristics of three types of lightning rods - blunt, sharp and flat. The objectives of this study are to determine the voltage breakdown characteristics of various types of lightning rods and to obtain the striking distance of each rod. A series of experiments were conducted in the high voltage laboratory consisting of individual testing rod, competitive testing rod and also horizontal distance changing. All three types of rods have been tested in each experiment in order to obtain a comprehensive result. The blunt rod has been proven as the best strike receptor in comparison to sharp and flat rod. This is because breakdown voltage for blunt rod is much lower (199 kV) than that of flat and sharp rod. Therefore, replacement of widely used sharp rod with the blunt one should be considered in order to provide better protection for buildings from lightning activities.Â 